Growth patterns and otolith shape variation in Citharus linguatula (Pisces: Pleuronectiformes) from two central Mediterranean areas exposed to different levels of fishing pressure - Emanuele Asciutto; Andrea Bellodi; Elisa Fodde; Maria Cristina Follesa; Francesco Longo; Maria Cristina Mangano; Pietro Battaglia (Regional Studies in Marine Science, 2026)

New records of rarely reported species in the Mediterranean Sea (July 2023) - DANIELE GRECH; EMANUELE ASCIUTTO; RIGERS BAKIU; PIETRO BATTAGLIA; CHAIMA BEN-GRIRA; ÖZNUR YAZILAN ÇAMLIK; ROBERTO CAPPUCCINELLI; LEILA CARMONA; SAHAR CHEBAANE; FABIO CROCETTA; ANDREA DESIDERATO; FILIPPO DOMENICHETTI; et al. (Mediterranean Marine Science, 2023)
This Collective Article presents new information about the occurrence of 23 marine taxa that belong to five Phyla: two Chlorophyta, one Annelida, six Mollusca, three Arthropoda, eleven Chordata (one Ascidiacea, one Elasmobranchii and nine Teleostei) and extending from the Western Mediterranean to the Levantine Sea. All these records were reported from nine countries from the western to the eastern Mediterranean Sea, with a broad biogeographical coverage as follows: Spain: first records of the sacoglossans Cyerce graeca and Placida tardyi for the Alboran Sea and first records of the nudibranch Marionia gemmii for the Mediterranean waters of Spain; first records of nudibranch Algarvia alba in the Mediterranean Sea. Italy: First report of the long-legged crab Paragalene longicrura, a further new Mediterranean record of the rare offshore rockfish Pontinus kuhlii, first documented record of the spiny butterfly ray Gymnura altavela in Sardinia (Tyrrhenian Sea), new record of the red‐spotted wrasse Lappanella fasciata from the Messina Strait, first documented record of the rarely observed brown moray Gymnothorax unicolor in the Ionian coast, first record of the colonial ascidian Botrylloides israeliensis, first record of the Morocco dentex Dentex maroccanus, first record of mottled shore crab Pachygrapsus maurus and of an adult specimen of barracudina Lestidiops sphyrenoides in the Adriatic Sea, and further new Mediterranean records of Ross worm Sabellaria spinulosa along the same coast. Tunisia: second record of smalleye squaretail Tetragonurus cuvieri from the African Mediterranean coast. Slovenia: first records of the sea slug Trapania graeffei and Melanochlamys wildpretii, with the last one also representing the northernmost finding of this species. Croatia: northernmost record of the endangered twaite shad Alosa fallax in the Adriatic coast. Albania: first records of the Mediterranean spearfish Tetrapturus belone. Türkiye: first record from the Aegean coasts for Türkiye of the green macroalgae Cladophora battersii and Valonia aegagropila. Israel: first record of the skeleton shrimp Caprella acanthifera in the Southeastern Mediterranean Sea. Syria: first record of the Smooth grenadier Nezumia aequalis from Syrian marine waters.

Growth of the Mesopelagic Fish Vinciguerria attenuata (Cocco, 1838) in the Strait of Messina (Central Mediterranean Sea) - Francesco Longo; Danilo Malara; Emanuele Asciutto; Pietro Battaglia (Journal of Marine Science and Engineering, 2023)
The age and growth of the slender lightfish Vinciguerria attenuata are investigated for the first time by the analysis of otolith microstructure. A total of 242 individuals (standard length range = 15.3–39.0 mm) are collected from the Strait of Messina (central Mediterranean Sea). The analysis of the length–weight relationship highlights a hyper-allometric growth for all specimens, while when males and females are analyzed separately, the results point out an isometric growth for males and hyper-allometric growth for females, although no statistical differences emerge comparing sex curves (p-value = 0.06). Microincrement readings are considered valid only for 214 sagittal otoliths. Microincrement counts range from 31 to 49 (average = 39.9) in the otolith central zone, 28 to 53 (average = 43.2) in the middle zone, and 15 to 332 (average = 136.1) in the external zone. Overall, total microincrements range between 75 and 418. Different growth models (von Bertalanffy, Gompertz and logistic models) are taken into account to select the best-fitting model in describing the growth patterns in V. attenuata. The logistic growth model is selected as the best-fitting model, and its parameters for all individuals are L∞ = 38.597, k = 0.0104 and I = 122.4.